Assisted Reproductive Technology and Retinopathy of Prematurity: 10.36351/pjo.v36i4.1130 - Tanveer, Raazia; Abid, Imrana (Pakistan Journal of Ophthalmology, 2020)
Although ART has changed the lives of many people, it has increased the burden on neonatologist and ophthalmologists with all types of complications related to prematurity in multiple births. In the last 20 to 25 years, there has been vast improvements in ART and neonatal intensive care, which has resulted in increased survival of most of the immature infants. There are specialized centers, which provide high?risk obstetric care, intensive neonatal care, use of steroids in the prenatal care, improved postnatal treatment with surfactant and nitric oxide and better respirators and advanced equipment for the care of extremely immature infants. All these have contributed to improved survival. Therefore, current changes in neonatal care warrant careful ongoing evaluation during the coming years regarding ROP.